Correlates of Brain Injuries in Women Subjected to Intimate Partner Violence: Identifying the Dangers and Raising Awareness. Issue 6 (3rd July 2019) - Valera, Eve M.; Campbell, Jacquelyn; Gill, Jessica; Iverson, Katherine M.
ABSTRACT: Awareness of the highly detrimental and long-term sequelae of brain injuries, and in particular repetitive mild traumatic brain injuries (mTBIs/concussions), has been rapidly growing. Specifically, there has been significant focus on repetitive mTBIs in male athletes and military personnel. Unfortunately, what is likely the largest group of repetitive mTBI sufferers, namely women who experience intimate partner violence (IPV), has received scant attention. Women experiencing IPV sustain both repetitive mTBIs at a high rate and also strangulation-related anoxic/hypoxic brain injuries. Due to biological, psychosocial and trauma-related differences between these women and the (mostly) men who have been studied to date, we cannot generalize what is learned from these studies to women suffering from IPV-related TBIs. Here we summarize some research aimed at understanding the occurrence and sequelae of IPV-related TBIs among various samples (i.e., women in shelters or primary care, from the community, veterans). These data show that IPV-related TBIs are highly prevalent, and associated with a range of negative cognitive and psychological outcomes as well as structural and functional brain connectivity. These associations could not be accounted for by potential confounds (e.g., abuse severity, psychiatric symptoms), making it clear that these negative health outcomes were not merely artifacts of being in an abusive relationship. We highlight gaps in research and provide recommendations for clinical practice. We present ideas for future research to elucidate the mechanisms underlying the associations noted above, in hopes of providing new insights into the links between TBIs and health risks in women who have experienced IPV.